UNDERSTANDING EMPHATIC BEHAVIOUR OF INTERPERSONAL FRIENDSHIP COMMUNICATION IN SOCIAL NETWORK PATH - Jana Miani Ulfah; Agus Naryoso, S.Sos, M.Si (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
Social networking Path is one of the private social media. Only those who had been friends with users who are mostly close relatives, who can see the activity in the social media. Because it is private, users will tend to open up to other users. They believe that other users will understand if they complaining in social media. However, users often have no empathy for other users. The emphatic behavior correlated with bullying, which can lead to conflict. The study aims to describe the experience of individual in understanding the behavior of empathy on Path. In this study, the researchers use the Emphatic Theory and Interpersonal Communication Theory. And also adds the Computer Mediated Communication Theory (CMC) to clarify the communication on social media. This study use qualitative research methods to research the type of phenomenology and descriptive approach. Subject were individuals who had friends and interacting on Path. Results from this study indicate that the social networking Path, the friendship relations that has existed enough will cause the more comfortable and relaxed interactions. So that will decrease misunderstandings and conflicts between them. If there is a conflict, it will not make their friendship lost. Empathetic behavior in social network, according to its users is to feel the other feeling by participating and doing things as we are in the position of other person. In this study it was found that interfere with the privacy and comfort of others is not empathetic behavior. Path also divert the written messages (comment) with just an emoticon. The presence of emoticons also affect how empathetic a person with another person. By giving emoticons, users will considered more responsive to others than those who don’t. The reciprocal by giving an emoticons on each post will arise a sense of respect to each other. Otherwise it will diminish a sense of closeness to one another because of the expectations that are not realized.